2016
DOI: 10.3389/fpls.2016.01338
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Anthocyanin-Related Genes by Transcriptomic Analysis of ‘Furongli’ Plum (Prunus salicina Lindl.) during Fruit Ripening Using RNA-Seq

Abstract: Anthocyanins are important pigments and are responsible for red coloration in plums. However, little is known about the molecular mechanisms underlying anthocyanin accumulation in plum fruits. In this study, the RNA-seq technique was used to analyze the transcriptomic changes during fruit ripening in the red-fleshed plum (Prunus salicina Lindl.) cultivar ‘Furongli’. Over 161 million high-quality reads were assembled into 52,093 unigenes and 49.4% of these were annotated using public databases. Of these, 25,681… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 105 publications
5
61
0
Order By: Relevance
“…The ‘Furongli’ plum ( Prunus salicina Lindl. ), with red peel and red pulp, has been cultivated in Fujian Province, China, for more than 700 years . Owing to its beneficial antioxidant potential and bioactive compounds, plum fruit has become a favorite for customers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ‘Furongli’ plum ( Prunus salicina Lindl. ), with red peel and red pulp, has been cultivated in Fujian Province, China, for more than 700 years . Owing to its beneficial antioxidant potential and bioactive compounds, plum fruit has become a favorite for customers.…”
Section: Introductionmentioning
confidence: 99%
“…), with red peel and red pulp, has been cultivated in Fujian Province, China, for more than 700 years. 17 Owing to its beneficial antioxidant potential and bioactive compounds, plum fruit has become a favorite for customers. Although the content of sugars, organic acids and some secondary compounds in plum fruit have been investigated in some detail, 17,18 the dynamics of anthocyanins, total phenolic compounds, flavonoids, soluble sugars, organic acids and related enzymes during plum fruit development are not fully understood in 'Furongli' cultivar.…”
Section: Introductionmentioning
confidence: 99%
“…The anthocyanin biosynthetic pathway is catalyzed stepwise by 11 major types of structural genes, including PAL (phenylalanine ammonia-lyase), C4H (cinnamate-4-hydroxylase), 4CL (4-coumaroyl: CoA-ligase), CHS (chalcone synthase), CHI (chalcone isomerase), F3H (flavanone 3-hydroxylase), F3'H (flavonoid 3'-hydroxylase), F3'5'H (flavonoid 3'5'-hydroxylase), DFR (dihydroflavonol 4-reductase), ANS (anthocyanidin synthase), and UFGT (UDP-glucose: flavonoid 3-O-glucosyltransferase) [6][7][8]. The pathway has been well studied and many structural genes have been identified in plants, including in Arabidopsis thaliana [9], apple [10], eggplant [11], Senecio cruentus [12], and sweet cherry [13].…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins are considered as effective markers for monitoring ripening stages and the organoleptic quality of fruits [25]. Fang et al [8] demonstrated that the color of 'Furongli' plum (Prunus salicina) changed from green to red during ripening, which was associated with an evident increase in the anthocyanin content, being 53.85-fold higher at 135 days after flowering (DAF) in comparison to that at 105 DAF. Similar phenomena have been documented in apple (Malus domestica) [26], grapevine (Vitis vinifera) [27], strawberry (Fragaria spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Expression patterns were drawn by Morpheus (https://software. broadinstitute.org/morpheus/) with defaulting parameters, and Pearson co-expression coefficient values were analyzed by CORREL formula within Excel 2016 [55,56].…”
Section: Transcription Factors and Transcriptional Regulators Identifmentioning
confidence: 99%